Energy Saving for Separately Excited DC Motor via Optimization Method - หอมจันทร์ จีรวรรณ; อารีรักษ์ กองพล; อารีรักษ์ ธิดารัตน์; อารีรักษ์ กองพัน (Srinakharinwirot University Engineering Journal, 2019)
The paper presents the comparison results about the energy saving of separately excited DC motor. The conventional and optimization methods are concerned for this comparison. The optimization method is applied to calculate the appropriate field current for loss minimization or energy saving. The experimental results show that the drive approach using the optimization method can save the energy consumed by the motor to 85.92% in maximum.